Everybody wins!: Poland hosts thrilling competitions of viruses, RNAi and football teams - Grimm, Dirk; Dalmay, Tamas; Rij, Ronald P. (EMBO reports, 2012)
The ESF-EMBO conference on ‘Antiviral RNAi: From Molecular Biology towards Applications’ took place in June 2012 in Pultusk, Poland. It brought together scientists working at the interface of RNAi and virus infections in different organisms, covering the complete range from basic mechanisms of RNA silencing to RNAi-based antiviral therapy.
Gesehen am 22.05.2018